SUCCESSFUL TREATMENT OF VENTILATOR ASSOCIATED PNEUMONIA CAUSED BY MULTIDRUG RESISTANT ACINETOBACTER BAUMANNII WITH A COMBINATION THERAPY OF CSE1034 AND COLISTIN: A CASE REPORT. - Garg, Himanshu; Dogra, Pratibha; Saxena, Mayank (Asian Journal of Pharmaceutical and Clinical Research, 2018)
Â Objective: One of the major causes of ventilator-associated pneumonia (VAP) in hospital settings is Acinetobacter baumannii. The propensity of acquiring antimicrobial resistance rapidly through a multiple number of mechanisms makes the selection of an appropriate empirical antimicrobial agent exceedingly challenging for this pathogen. Methods: The present case report explores the option of treating VAP infection due to carbapenem-resistant pathogens with antibiotic adjuvant entities. Results: We present a case of VAP due to carbapenem-resistant A. baumannii that was successfully treated with CSE-1034 and colistin combination therapy. Conclusion: Early recognition and appropriate antibiotic therapy are essential to eliminate poor outcomes in multidrug-resistant (MDR) bacterial infections. The present case highlights the antibiotic adjuvant entity CSE-1034â€ as an empiric option for the treatment of VAP due to MDR A. baumannii in intensive care unit.